A COMPREHENSIVE META-ANALYSIS AND REVIEW ON THE ANTIARTHRITIC EFFECTS OF CAMPESTEROL: INSIGHTS INTO MECHANISTIC ACTION - NAZIR , S; MOBASHAR , A; CHAUDHARY , WA; JAVAID , S; ASIF , K; SIDDIQUE , M (Biological and Clinical Sciences Research Journal, 2023)
Delving into the potential therapeutic benefits of Campesterol, a plant-derived sterol, this comprehensive metaanalysis and review systematically dissect its role in combating arthritis. The focus is primarily on the reported ability of Campesterol to suppress vital proinflammatory markers such as TNF-α, IL1β, IL-6, NFκ-B, MMP-3, COX-I, and COX-II, and its potential to stimulate the anti-inflammatory cytokine IL-4. Rheumatoid arthritis (RA) is a chronic inflammatory condition recognized for deleterious impact on joint structures. This meta-analysis and review aim to elucidate the potential therapeutic advantages of Campesterol, a phytosterol renowned for its anti-inflammatory properties, in managing rheumatoid arthritis (RA). Through the systematic compilation of evidence from various studies, our objective is to elucidate the precise mechanism of action by which Campesterol exerts its antiarthritic effects. This meta-analysis, conducted in adherence to the PRISMA guidelines, encompasses studies until July 2023. The primary objective is to comprehend the function of Campesterol in regulating both pro and anti-inflammatory indicators in rheumatoid arthritis (RA). The reliability of the studies included in the analysis was assessed using standardized evaluation instruments. A noteworthy study conducted on a rat model with arthritis induced by CFA (Complete Freund's Adjuvant) presents compelling evidence supporting the antiarthritic properties of Campesterol. Administration of Campesterol resulted in a notable decrease in arthritic scores, paw edema, and levels of proinflammatory cytokines, including TNF-α, NFκ-B, IL-6, COX-II, and IL-1. Additionally, the levels of PGE-2 were also reduced. Moreover, it elicited an increase in anti-inflammatory interleukin4 (IL-4) levels and restored homeostasis in blood and biochemical parameters, indicating a comprehensive amelioration in the pathology of arthritis. These findings were further supported by additional studies, highlighting the potential of Campesterol as a potent therapeutic agent in managing rheumatoid arthritis (RA). This meta-analysis strongly supports the therapeutic potential of Campesterol in treating arthritis. However, additional research, particularly involving human trials, is required to substantiate these findings and gain a comprehensive understanding of the therapeutic potential of Campesterol in the management of arthritis. Further investigations are warranted to explore the intricate aspects of Campesterol's pharmacokinetics and pharmacodynamics and its enduring safety profile. Additionally, it is imperative to examine the potential synergistic interactions that may arise when Campesterol is combined with established treatments for rheumatoid arthritis (RA). It is imperative to investigate Campesterol's precise molecular targets further.